DI-006 Prescription pattern of molecular targeted therapy in metastatic renal cell carcinoma. (24th February 2014) - Amorós, P; Bastida, C; Do Pazo, F; Creus, N; Codina, C
Abstract : Background: Several molecular targeted agents (MTA) have been approved recently for the treatment of metastatic renal cell carcinoma (mRCC). However data on the use of these drugs in clinical practice are limited. Purpose: To describe the prescription patterns of MTA (sunitinib, pazopanib, sorafenib, everolimus, temsirolimus and bevacizumab) in patients with mRCC in a tertiary hospital. Materials and methods: Retrospective observational study of all patients who received at least one cycle of MTA for the treatment of mRCC from August 2006 to January 2013. Variables obtained from the computer system included date of birth, sex, tumour histology (predominant clear cell histology (CCH) or non-clear cell histology (n-CCH)), treatment line number and first and last dispensing date. Results: 83 patients, average age of 63 (SD ± 10.6) (81% male), were dispensed at least one treatment of MTA. 72% of patients showed predominantly CCH. The median length of treatment was 10 months (range 0.4–66.9). Most of the patients with CCH (n = 59) received sunitinib (n = 42; 71%) or sorafenib (n = 10; 17%) as first-line treatment. 24 patients went through a second line: mainly sorafenib (n = 9; 38%) and sunitinib (n = 6; 25%). 5 patients continued with sunitinib, sorafenib or everolimus as third line. n-CCH patients (n = 24) were treated with sunitinib (n = 18; 75%), sorafenib (n = 3; 13%), or temsirolimus (n = 3; 13%) as first line. Eleven patients received a second-line treatment, principally sunitinib (n = 4; 36%), sorafenib (n = 3; 27%) and temsirolimus (n = 2; 18%). A third line was prescribed to 3 patients (2 temsirolimus and 1 sorafenib). Only 3 patients were retreated with the same drug. Conclusions: Sunitinib, followed by sorafenib, are the most commonly used drugs in all lines and histologies of mRCC. Further studies are needed to evaluate any trends in use after pazopanib's recent approval. No conflict of interest.